迟子建文学作品中保护意识的产生、展现及意义 = Formation, presence and significance of protection consciousness in Chi Zijian’s literature work - 高畅 Gao, Chang (2019)
迟子建近年来备受瞩目，获了中国多项文学类奖项她对家乡的情感影响了她的作品，因此作品中展现出了对于自然、女性甚至动植物的保护意识。本文将以作者本身对地方的认知和认同感为基础，进一步了解这种保护意识的产生。并运用生态女性主义理论分析作品中保护意识的展现和意义。 Chi Zijian has attracted a lot of attention in recent years. Her affection for her hometown has influenced her literature work, the work shows her environmental protection consciousness and female consciousness. Based on author’s understanding and cultural identity recognition of her hometown, the paper will discuss the formation of her environmental protection consciousness and being feminine. the theory of ecofeminism will be used to analyze the presence and significance of these protection consciousness in her literature work.